2004
DOI: 10.4314/wiojms.v2i2.28433
|View full text |Cite
|
Sign up to set email alerts
|

Standing Stock, Agar Yield and Properties of <i>Gracilaria salicornia</i> Harvested along the Tanzanian Coast

Abstract: Abstract-Seasonal biomass variation and agar yield of G. salicornia (C. Ag.) Dawson from Oyster Bay, Dar es Salaam, and Chwaka Bay, Zanzibar, were determined, and some properties of the agar examined. Mean biomass and canopy cover values ranged from 21-60 g/m 2 and 7-20 %, respectively. The highest mean biomass and cover values were obtained during the SE monsoon. Agar yield varied from 13.7 to 30.2 % (dry weight) and was highest during the dry NE monsoon period. Alkali treatment generally reduced agar yield b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
18
4
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 39 publications
5
18
4
3
Order By: Relevance
“…Preparation of low-gel-strength (210 g cm −2 ) agar from G. salicornia has been reported in the literature (Oyieke 1993;1994;Calumpong et al 1999). Seasonal biomass variation and extraction of low-gel-strength agar from G. salicornia and G. debilis from Tanzania, including application in culture of microorganisms have been reported (Buriyo and Kivaisi 2003;Kivaisi and Buriyo 2007). The prior reports on agars from these two Gracilaria species revealed that these are the source of low quality agars.…”
Section: Introductionmentioning
confidence: 95%
“…Preparation of low-gel-strength (210 g cm −2 ) agar from G. salicornia has been reported in the literature (Oyieke 1993;1994;Calumpong et al 1999). Seasonal biomass variation and extraction of low-gel-strength agar from G. salicornia and G. debilis from Tanzania, including application in culture of microorganisms have been reported (Buriyo and Kivaisi 2003;Kivaisi and Buriyo 2007). The prior reports on agars from these two Gracilaria species revealed that these are the source of low quality agars.…”
Section: Introductionmentioning
confidence: 95%
“…Kualitas dan kuantitas agar rumput laut Gracilaria sp., dipengaruhi oleh variasi musim dan spesies rumput laut (Hurtado-Ponce, 1994;Givernaud et al, 1999, Buriyo & Kivaisi, 2003. Terdapat hubungan yang terbalik antara kandungan agar dan biomassa rumput laut, di mana faktor lingkungan yang berhubungan dengan tingginya kandungan agar adalah salinitas, suhu, dan ketersediaan nitrogen (Buriyo & Kivaisi, 2003).…”
Section: Kandungan Agarunclassified
“…Terdapat hubungan yang terbalik antara kandungan agar dan biomassa rumput laut, di mana faktor lingkungan yang berhubungan dengan tingginya kandungan agar adalah salinitas, suhu, dan ketersediaan nitrogen (Buriyo & Kivaisi, 2003). Selama periode pertumbuhan optimal, rumput laut secara bertahap akan mengakumulasi nitrogen sebagai cadangan nutrien pada saat kandungan nutrien yang rendah, intensitas cahaya yang tinggi, suhu, dan salinitas yang tinggi.…”
Section: Kandungan Agarunclassified
“…Therefore, it is necessary to standardise the extraction process to optimise the agar yield and quality. In general, agar extraction is done in a waterbath or autoclave and there is no account mentioned of any preference of one over another, except for Buriyo and Kivaisi (2003) who reported that agar yield is higher using an autoclave than a waterbath. Generally, Gracilaria species produce agars with low quality due to their high sulphate concentrations.…”
Section: Post -Harvest: Agar Extractionmentioning
confidence: 99%